The Effect of Idealism, Relativism, Love of Money, and Academic Experience on Ethical Perception of Accounting Students (Case Study on Accounting Students of Muhammadiyah University of Surakarta) - Diva Nanda Ayuk Agustina; Triyono (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of Idealism, Relativism, Love of Money, and Academic Experience on the Ethical Perception of accounting students at Universitas Muhammadiyah Surakarta. Drawing on Forsyth’s Ethics Position Theory, Idealism reflects a belief in universal moral principles, while Relativism denotes ethical flexibility based on context; Love of Money represents a value orientation that may conflict with ethical behavior. Using a quantitative approach, data were collected via online questionnaires from 945 undergraduate accounting students through convenience sampling. Variables were measured using established instruments such as the Ethics Position Questionnaire (EPQ) and the Love of Money scale. Multiple linear regression was applied after verifying assumptions of normality, multicollinearity, and homoscedasticity. Results indicate that Idealism and Academic Experience significantly enhance ethical perception, suggesting that students with strong moral ideals and greater academic exposure are more ethically aware. Conversely, Relativism and Love of Money showed no significant effect, potentially due to cultural or educational factors that prioritize integrity over personal values. These findings highlight the importance of moral conviction and structured academic learning in fostering ethical development, while pointing to the limited influence of relativistic thinking and financial motivation in this context.